Intra-couple wealth inequality: What's demographics got to do with it? - Miriam Rehm; Alyssa Schneebaum; Barbara Schuster (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2022)
Existing literature shows that on average and across countries, men have higher levels of wealth than women. However, very little is known about the gender-specific wealth gap within couples. This paper studies this phenomenon. The particular focus of the paper is on the relationship between the demographic characteristics of the couple and the couple's gender wealth gap. We focus on how age, education, marital status, fertility, and migration background are related to the wealth gap within a couple. In both univariate and multivariate analyses, we find that the strongest demographic predictors of an intra-couple wealth gap are the age gap between the members of the couple; the highest level of education; and the composition of migration background in the couple. The gender wealth gap is particularly high in couples with a native-born man and a foreign-born woman.
Keywords: 330